2019
DOI: 10.1061/(asce)me.1943-5479.0000667
|View full text |Cite
|
Sign up to set email alerts
|

Barriers Affecting Effective Application of Anticorruption Measures in Infrastructure Projects: Disparities between Developed and Developing Countries

Abstract: This study examines the critical barriers that obstruct the full potency and the intended effectiveness of anti-corruption measures enforced to mitigate the pervasiveness of corrupt practices in project procurement and execution. To achieve this aim, a comprehensive review of literature was conducted and resulted in the identification of 17 critical barriers. A questionnaire survey was conducted with 65 experts from around the world involved in infrastructure project procurement and management using the purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 40 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Based on an extensive review of the relevant literature [6,52,53], the questionnaire survey was chosen as the main data instrument to solicit the opinions on the subject matter. In order to encourage participation, the questionnaire was completely anonymous and voluntary, respondents were assured of the confidentiality of their data [54]. No reminder letter was sent to the respondents during the data collection process.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…Based on an extensive review of the relevant literature [6,52,53], the questionnaire survey was chosen as the main data instrument to solicit the opinions on the subject matter. In order to encourage participation, the questionnaire was completely anonymous and voluntary, respondents were assured of the confidentiality of their data [54]. No reminder letter was sent to the respondents during the data collection process.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…We have the questionnaire interpreted into French, Russian, Arabic, Portuguese, Spanish, Italian, Indonesian, and Chinese. (Kingsford & Chan, 2019). The Cronbach's alpha reliability test (Likert scale bigger than 0.7) justified that the chosen scale was suitable, the data collection instrument was strongly reliable, and the responses were consistent with the survey (Shen, Lu, Peng, & Jiang, 2011;SPSS, 2006).…”
Section: Demographic and Geographical Profilementioning
confidence: 92%
“…Studies by Santoso and Bourpanus (2018) and Liao et al (2002), showed that one motivation for organizations to adopt e-procurement was to reduce bid collusion and corrupt practices. The procurement process in the construction and engineering sector is highly vulnerable to corrupt practices (Transparency International, 2005; Owusu and Chan, 2018), hence organizations employ e-procurement to curb these corrupt practices. Increase competition among contractors/suppliers is an additional driver that motivates organizations to adopt e-procurement for projects.…”
Section: Classification Of Drivers Of E-procurement For Project Procurementmentioning
confidence: 99%